2010
DOI: 10.5152/akd.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the regional myocardial deformation changes and viability in anterior acute myocardial infarction patients by strain and strain rate imaging

Abstract: Assessment of the regional myocardial deformation changes and viability in anterior acute myocardial infarction patients by strain and strain rate imagingAnteriyor akut miyokart enfarktüslü hastalarda bölgesel miyokardiyal deformasyon değişiklikleri ve canlılığın gerilme ve gerilme oranı görüntülemesi ile değerlendirilmesi Original Investigation Özgün Araşt›rma 479Address ABSTRACTObjective: To prospectively evaluate the regional myocardial deformation changes and viability in anterior acute myocardial infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In the study of Aksakal et al (26), as in current study, it was indicated that, after successful PCI, important left ventricular echocardiographic parameters were recovered. We planned to conduct our study via (with) conventional echocardiography method, since tissue Doppler and strain echocardiography was not available in our hospital in that period of time.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In the study of Aksakal et al (26), as in current study, it was indicated that, after successful PCI, important left ventricular echocardiographic parameters were recovered. We planned to conduct our study via (with) conventional echocardiography method, since tissue Doppler and strain echocardiography was not available in our hospital in that period of time.…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, tissue Doppler and strain rate echocardiography have been used for determining the left ventricular contractility and vitality and its superiority to conventional echocardiography methods was shown (25,26). In the study of Aksakal et al (26), as in current study, it was indicated that, after successful PCI, important left ventricular echocardiographic parameters were recovered.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Strain echocardiography has been used in the quantitative assessment of LV contractile function in many cardiovascular diseases (9)(10)(11)(12). Initially myocardial deformation was assessed by tissue Doppler imaging derived S. But the most important limitation of this technique is angle-dependent and deformation can only be assessed longitudinally (8,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…All data were acquired at a high frame rate of >120 frame/s. Utmost attention was paid to keep the region of interest at the center of the ultrasound sector to ensure an alignment as close to 0 as possible to long-axis motion (4)(5)(6)(7)15). In all the samples studied, we always selected three consecutive cardiac cycles, which were used for subsequent analysis.…”
Section: Color Doppler Myocardial Imagingmentioning
confidence: 99%